Impact of pulmonary infection on thoracoscopic surgery outcomes in children with CPAM: a retrospective study - Cui-xia Yuan; Chun Wu; Zheng-Xia Pan; Yong-Gang Li (BMC Surgery)
Abstract Background Pulmonary infection is a common clinical complication in children with congenital pulmonary airway malformation (CPAM). Surgical intervention has been proven effective in managing this condition. We aim to evaluate the impact of pulmonary infection on the outcomes of total thoracoscopic procedures in children with CPAM. Methods This was a single-center retrospective study. CPAM patients who underwent total thoracoscopic surgery at a tertiary care center from January 2013 to December 2023 were divided into three groups based on pulmonary infection status: non-infection (NI), hidden infection (HI), and pulmonary infection (PI). Clinical characteristics and operation-related outcomes were compared among the groups. Results A total of 154 children with CPAM who underwent thoracoscopic surgery were categorized into three groups based on pulmonary infection: the NI group (27 cases), HI group (56 cases), and PI group (71 cases). The conversion rate to thoracotomy was 14.8%, 23.2%, and 29.2% respectively across the three groups. 116 cases were successfully completed thoracoscopically. There were no significant differences in gender distribution among the three groups (p > 0.05), but statistically significant (p < 0.05) in age and weight. Significant differences emerged in operative time and blood loss (p < 0.05), but no significant variations were found in transfusion requirements, chest tube duration, ventilator use duration, or hospital stay length (p > 0.05). In postoperative pulmonary complications, a statistically significant difference was found regarding pneumothorax incidence among all three groups (p < 0.05), whereas no significant differences (p > 0.05) emerged concerning atelectasis or pneumonia incidences across these cohorts. Conclusions Pulmonary infection is the most prevalent complication in CPAM and exhibits a high rate of hidden infections, thereby complicating surgical intervention and increasing associated risks. Early thoracoscopic intervention prior to infection manifestation can optimize surgical outcomes and reduce associated complications.